Differentiation, evolution and utilization of natural alleles for cold adaptability at the reproductive stage in rice. Issue 12 (24th June 2020) - Guo, Haifeng; Zeng, Yawen; Li, Jilong; Ma, Xiaoqian; Zhang, Zhanying; Lou, Qijin; Li, Jin; Gu, Yunsong; Zhang, Hongliang; Li, Jinjie; Li, Zichao
Abstract: Genetic studies on cold tolerance at the reproductive stage in rice could lead to significant reductions in yield losses. However, knowledge about the genetic basis and adaptive differentiation, as well as the evolution and utilization of the underlying natural alleles, remains limited. Here, 580 rice accessions in two association panels were used to perform genome‐wide association study, and 156 loci associated with cold tolerance at the reproductive stage were identified. Os01g0923600 and Os01g0923800 were identified as promising candidate genes in qCTB1t, a major associated locus. Through population genetic analyses, 22 and 29 divergent regions controlling cold adaptive differentiation inter‐subspecies ( Xian / Indica and Geng / Japonica ) and intra‐ Geng, respectively, were identified. Joint analyses of four cloned cold‐tolerance genes showed that they had different origins and utilizations under various climatic conditions. bZIP73 and OsAPX1 differentiating inter‐subspecies evolved directly from wild rice, whereas the novel mutations CTB4a and Ctb1 arose in Geng during adaptation to colder climates. The cold‐tolerant Geng accessions have undergone stronger selection under colder climate conditions than other accessions during the domestication and breeding processes. Additive effects of dominant allelic variants of four identified genes have been important in adaptation to cold in modern rice varieties. Therefore, this study provides valuable information for further gene discovery and pyramiding breeding to improve cold tolerance at the reproductive stage in rice.